Perancangan Quality Plan Daging Ayam Kapas di Peternakan XYZ - Michael Eka Putra (Jurnal Titra, 2019)
Chicken farm must concern about their production process. Farm XYZ just started selling cotton chicken meat to supermarket in 2019. The problem of farm XYZ is returns from supermarket, because of the quality of the chicken’s meat. Farm XYZ does not have structured quality control system. The aim of this research is making quality plan for farm XYZ so that the number of returns can be reduced. Five why analysis was use to analyze the problem. The final result of the research is the design of quality plan based on the order of the production process.